2022
DOI: 10.3390/jcdd9020059
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play after SARS-CoV-2 Infection in Competitive Athletes of Distinct Sport Disciplines in Italy: A FMSI (Italian Federation of Sports Medicine) Study

Abstract: Background: SARS-CoV-2 can lead to several systemic complications, including myocardial injuries; these might be worsened by heavy physical activity. The optimal approach to cardiac risk stratification following SARS-CoV-2 infection in athletes for a safe return to play (RTP) still needs defining. The aim of this study was to assess the prevalence of abnormal RTP test results, according to the protocol of Italian Federation of Sport Medicine (FMSI), which was endorsed by the Italian Ministry of Health, potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
1
19
1
3
Order By: Relevance
“…10 One study of athletes ages 18-35 years indicated that about half of athletes with COVID-19 were symptomatic 30 days after the initial COVID-19 infection, with 1.2% having moderate or severe symptoms. 13 Previous research on athletes has shown that Long COVID, in particular cardiac symptoms, can occur and that the physiological impact of COVID-19, including on heart rate, lasts 2-3 months on average. [14][15][16] There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…10 One study of athletes ages 18-35 years indicated that about half of athletes with COVID-19 were symptomatic 30 days after the initial COVID-19 infection, with 1.2% having moderate or severe symptoms. 13 Previous research on athletes has shown that Long COVID, in particular cardiac symptoms, can occur and that the physiological impact of COVID-19, including on heart rate, lasts 2-3 months on average. [14][15][16] There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, many athletes were affected by COVID-19, prevalently in a mild form [ 16 ]. Among the variety of symptoms reported by the general population, muscle soreness, fatigue, and weakness were very frequent, making it highly likely that the COVID-19 disease could induce muscle tissue damage and more severe clinical manifestations in the lung, cardiac, and neural tissues [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in these studies no data on pre-COVID cardiovascular evaluation were available and the number of subjects recruited was low. More recently, a report from the Italian Federation of Sport Medicine collecting data on more than 4100 athletes reported a 2.4% of ventricular arrhythmias by exercise test or 24 hour ECG monitoring and myocarditis diagnosed in 0.12% 27 .…”
Section: Discussionmentioning
confidence: 99%